PENERAPAN UANG MUKA DI CATERING AULIA DAN CATERING HJ. WATI PERSFEKTIF EKONOMI ISLAM DI KOTA PALANGKA RAYA - Hafizi, Muhammad Riza; Jelita, Jelita; Aulia, Deanti (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
Catering becomes a solution to consumers who want to fulfill their needs and wants without having to waste time and energy. This is also a challenge for a catering businessman to maintain and keep improving their service quality from time by time so can keep satisfying consumers. In the payment system, catering business is using down payment system. According to that case, to understand more about how the down payment application in Islamic economics perspective need to studied more details. This research aimed to analyze and understand (1) How are the down payment application of Catering Aulia and Catering Hj. Wati in Palangkaraya City. (2) How the buying and selling system with the down payment in Islamic economics perspective.The result of this research is the application of down payment in Catering Aulia and Catering Hj. Wati is an 'urf or a habit that is done both for catering owners and their customers. Application of down payment in catering payments in terms of the usual materials included in the 'urf fi'li, while in terms of good and bad judgments included into 'urf shahih. In practice, both in Catering Aulia and Catering Hj. Wati the amount of down payment is not specified. And if there is an order cancellation then the down payment will be refunded in full except at certain moments. Implementation of down payment viewed in terms advantages may be done as long as no party feels disadvantaged. Down payment made to avoid any breach between the catering owners and consumers.